Os procedimentos de aplicação da desconsideração da personalidade jurídica no direito brasileiro - Artur Andrade Santos (2019)
The doctrine of corporate veil piercing allows to ignore the limited liability, inorder to reach the assets of third parties, who have abused the mentionedprerogative, usually within the scope of companies. The institute and theassumptions of its application, included in different legal norms of Brazilian law, havebeen the subject of various studies, considering the relevant role that businessactivities plays in society. However, it is also important to analyze which procedureshould be adopted in order for the veil-piercing doctrine to be correctly applied, as animperative of legal certainty and observance of the principles of audi alteram partemand defense, constitutionally provided. The 2015 Brazilian Code of Civil Procedure, inits articles 133 to 137, represented a great advance in the matter, bringing generalforecasts about the procedural norms to be observed when the limited liability shouldbe disregarded. However, even if the subsidiary and subsidiary application of theCode of Civil Procedure is foreseen in procedures regulated by other standards, it isnecessary to analyze how the specific branches of law may use the new provisions inregard to disregard, considering the specialties and principles of each area. Thus, themain objective of this study is to analyze which procedures shall be adopted forpiercing the corporate veil, observing the different hypotheses in which it is foreseenin the Brazilian legal system .